Response of the Subtropical Gyre Circulation in the North Pacific Ocean to CO2 Quadrupling. Issue 4 (8th August 2019) - Li, Qiuxian; Luo, Yiyong; Liu, Fukai
ABSTRACT: This study investigates the response of the subtropical gyre circulation in the North Pacific Ocean to quadrupled CO2 using the Community Earth System Model, version 1 (CESM1). In particular, an overriding technique is applied to isolate and quantify the effects of wind stress and thermal warming caused by CO2 emissions. Results show that, in response to the increase in CO2, the total mass transport in the subtropical gyre is reduced by approximately 11%. This reduction results mainly from negative anomalies of the wind stress curl over the subtropical region, with a smaller contribution from the thermal warming effect. Furthermore, a detailed analysis finds that the change in the subtropical gyre is baroclinic in nature [i.e., the gyre appears to be spin-up in the upper ocean (above 300 m) but spin-down in the lower thermocline (from 300 to 1500 m)]. This reversal between the upper ocean and lower thermocline is a result of the thermal warming effect, which intensifies ocean stratification, hindering the transfer of momentum from the upper layers to the lower layers and leading to an acceleration of the gyre in the upper ocean but a deceleration in the lower thermocline. Another feature of the response of the subtropical gyre to quadrupled CO2 is the respective poleward and equatorward movements of its northern and southern boundaries, which is a result of the change in the zero wind stress curl lines.